PHATIC UTTERANCE ON MOVIE FLYING COLORS BY NOBUHIRO DOI - Yuniarsih; Eky Kusuma Hapsari; Andre Anugraha (Universitas WIdyatama, 2021)
The object of this thesis was phatic communication. The purpose of this study was aimed to know and reveal the shapes and fuction of the phatic utterance in communication that japanese is super phatic type of society. This thesis was using Nabuhiro Doi‘s Flying Colors as data source. This study was using descriptive qualitative as the method of analysis, and using documentation technique, notes and listening technique to collect the data. Speech and SPEAKING are useful for knowing the utterance about whom, norms, purpose, etc in the communication. This thesis found that phatic utterance has seven shapes which are praise utterance, grateful utterance, appologize utterance, greeting utterance, encourage utterance, and small talk utterance. This thesis also has three utterance function which are, to open communication, to break the silence and to close the communication.